IMPLEMENTATION OF EMERGENCY INSTALLATION SERVICE MANAGEMENT IN WEST JAVA PROVINCE MENTAL HOSPITAL ON PATIENT FAMILY SATISFACTION - Hanafi, Muhammad; Atmawinata, Maya R (Universitas Ibn Khaldun Bogor, 2024)
Emergency care or triage is a system of prioritizing patients based on their severity or urgency that requires immediate action. Based on this, service officers in the emergency room must have special abilities. The success of a hospital service program is patient satisfaction because of a factor that is used as a determinant. Realizing patient satisfaction with mental nursing services certainly refers to various factors. There are 5 factors, namely: Tangibles, Reliability, Responsiveness, Assurance, Understanding Consumer Needs. This research uses quantitative with data collection methods through questionnaires and regression data analysis techniques. The population of this study were 40 families of patients of the Emergency Intalasi of the West Java Provincial Mental Hospital. After taking and processing data in the form of statistical tests SPSS version 25, the results obtained are the influence between the West Java Provincial Mental Hospital Emergency Room services on patient family satisfaction. Apart from the service variable (X) which is very influential on patient family satisfaction is the tangibles indicator with a very good category. Meanwhile, the variable of patient family satisfaction (Y) which has the greatest influence on the satisfaction of the patient's family itself is the indicator of conformance to specifications.